2020
DOI: 10.1186/s10194-020-01110-9
|View full text |Cite
|
Sign up to set email alerts
|

A global real-world assessment of the impact on health-related quality of life and work productivity of migraine in patients with insufficient versus good response to triptan medication

Abstract: Background Migraine is a chronic, disabling neurological disease characterized by moderate-to-severe headache pain with other symptoms, including nausea, vomiting, and photophobia. Triptans, while generally effective, are insufficiently efficacious in 30–40% of patients and poorly tolerated by or contraindicated in others. We assessed the impact of insufficient response to triptans on health-related quality of life (HRQoL) and work productivity in patients currently receiving any prescribed tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 48 publications
(59 reference statements)
4
46
4
2
Order By: Relevance
“…However, insufficient responders to acute treatment were more likely than sufficient responders to exhibit greater migraine severity, as indicated by the higher proportions of insufficient responders with a clinical diagnosis of chronic migraine or medication-overuse or tension-type headache and the greater requirements of insufficient responders for extra doses of prescribed acute medication to relieve pain symptoms or symptoms of a migraine attack. Headache-related disability was also significantly greater and HRQoL significantly lower in Japanese insufficient responders to acute treatment than in sufficient responders, and similar findings have been reported in the overall 2017 analysis of Adelphi Migraine DSP data from USA, France, Germany, Italy, Spain, and the UK [20] and in the 2014 US Adelphi Migraine DSP [19].…”
Section: Discussionsupporting
confidence: 78%
“…However, insufficient responders to acute treatment were more likely than sufficient responders to exhibit greater migraine severity, as indicated by the higher proportions of insufficient responders with a clinical diagnosis of chronic migraine or medication-overuse or tension-type headache and the greater requirements of insufficient responders for extra doses of prescribed acute medication to relieve pain symptoms or symptoms of a migraine attack. Headache-related disability was also significantly greater and HRQoL significantly lower in Japanese insufficient responders to acute treatment than in sufficient responders, and similar findings have been reported in the overall 2017 analysis of Adelphi Migraine DSP data from USA, France, Germany, Italy, Spain, and the UK [20] and in the 2014 US Adelphi Migraine DSP [19].…”
Section: Discussionsupporting
confidence: 78%
“…Increased physician awareness may help better identify patients at risk of insufficient response to triptans [55]. In addition to factors identified here, overuse of over-the-counter (OTC) medication and timing of triptan administration were factors identified in a global real-world study using data obtained from physicians and patients.…”
Section: Discussionmentioning
confidence: 80%
“…Patient-Reported Outcomes (PROs) are mostly used in clinical research rather than in clinical practice. However, some PRO tools such as Migraine-Specific Quality of Life Questionnaire (MSQ) and Migraine Disability Assessment (MIDAS), although not specific to acute treatment, might give an idea of impact of attacks [55]. Further, it might be helpful to have some potential specific PRO tools such as Migraine Treatment Optimization Questionnaire (MTOQ) for the acute treatment which may aid physicians in identifying when to consider reassessment of migraine treatment options [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that productivity loss is less when early migraine treatment is applied, and when pain is not moderate to severe, either with triptan or non-triptan treatment [11,13]. Migraine patients treated with triptans showed that those with an insufficient response to triptan medication have significantly worse health-related quality of life and are less productive than those who respond to triptans [17]. Furthermore, pharmacoeconomic research demonstrated that early interventions with triptans have more benefits than delayed interventions do [13,14].…”
Section: Introductionmentioning
confidence: 99%